Temperature-controlled ablation of the mitral isthmus line using the novel DiamondTemp ablation system - Rottner, Laura; My, Ilaria; Schleberger, Ruben; Moser, Fabian; Moser, Julia; Kirchhof, Paulus; Ouyang, Feifan; Rillig, Andreas; Metzner, Andreas; Reissmann, Bruno (Frontiers in Cardiovascular Medicine, 2022)
Background The novel DiamondTemp™ (DT)-catheter (Medtronic®) was designed for high-power, short-duration ablation in a temperature-controlled mode. Aim To evaluate the performance of the DT-catheter for ablation of the mitral isthmus line (MIL) using two different energy dosing strategies. Materials and methods Twenty patients with recurrence of atrial fibrillation (AF) and/or atrial tachycardia (AT) following pulmonary vein (PV) isolation were included. All patients underwent reisolation of PVs in case of electrical reconnection and ablation of a MIL using the DT-catheter. Application durations of 10 (group A, n = 10) or 20 s (group B, n = 10) were applied. If bidirectional block was not reached with endocardial ablation, additional ablation from within the coronary sinus (CS) was conducted. Results In 19/20 (95%) patients, DT ablation of the MIL resulted in bidirectional block. Mean procedure and fluoroscopy time, and dose area product did not differ significantly between the two groups. In group B, fewer radiofrequency applications were needed to achieve bidirectional block of the MIL when compared to group A (26 ± 12 vs. 42 ± 17, p = 0.04). Ablation from within the CS was performed in 8/10 patients (80%) of group A and in 5/10 (50%) patients of group B (p = 0.34). No major complication occurred. Conclusion Mitral isthmus line ablation with use of the DT-catheter is highly effective and safe. Longer radiofrequency-applications appear to be favorable without compromising safety.